Od brezpogojne k pogojevani državi blaginje - spremembe znotraj koncepta državljanstva - Kopač, Anja (Družboslovne razprave, 2005)
Rights and obligations are one of the most important dimensions of citizenship. They define the position of individuals versus the community/state. In resent years there is an obvious shift from understanding rights as an absolute claims to understanding them as negotiated claims , whereas the work is central for assuring a full citizenship. Contemporary citizenship debates are focused around the question of right balance 366 between rights and obligations, and it seems that they are no longer preoccupied with the question of admissibility of conditionality. However, liberal and communitarian approach to citizenship and left and right political orientations offer different views on what should be considered as the right balance. Nevertheless, the contemporary concept of citizenship has moved from Marshall's universal, unconditional citizenship guaranteed by the strong national (welfare) state toward the conditional citizenship which offers to deserving individuals help to actively face new social risks. Changes introduced within the concept of citizenship have an important influence on the welfare state and are crucial for the understanding of social reform.
Keywords: država; state; pravice; socialna država; welfare state; država blaginje; socialna varnost